2004
DOI: 10.1007/bf02931386
|View full text |Cite
|
Sign up to set email alerts
|

High level of resistance to metronidazole and clarithromycin inHelicobacter pylori isolated from pediatric patients in Poland (1997–2001)

Abstract: Resistance to metronidazole (Met), clarithromycin (Cla) and amoxycillin (Amo) was examined using H. pylori isolates from child patients before and after treatment in the period 1997-2001. The rate of Met and Cla resistance before treatment was 35.2 and 8.6%, respectively. Six weeks after treatment 48.4% of the isolated strains were resistant to Met and 17.6% to Cla. The highest rate of resistance to both antibiotics was determined in 2001 (before treatment, 46 and 15%, respectively, and after treatment, 57.8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…studied resistance to MET, CLA, and AMO using H. pylori isolates from children before and after treatment. The rate of MET and CLA resistance before treatment was 35% and 9%, and 6 weeks after treatment it was 48% and 18%, respectively . A similar observation was made by Miyaji et al., who concluded that the failure of treatment could be a consequence of the induction of resistance to CLA and MET.…”
Section: Discussionsupporting
confidence: 73%
“…studied resistance to MET, CLA, and AMO using H. pylori isolates from children before and after treatment. The rate of MET and CLA resistance before treatment was 35% and 9%, and 6 weeks after treatment it was 48% and 18%, respectively . A similar observation was made by Miyaji et al., who concluded that the failure of treatment could be a consequence of the induction of resistance to CLA and MET.…”
Section: Discussionsupporting
confidence: 73%
“…The reported resistance of H. pylori in treated children and adults (35-68 % to metronidazole, 17-63 % to clarithromycin and 15-73 % to metronidazole+clarithromycin) can hinder the success of eradication (Chisholm et al, 2007;Gosciniak et al, 2004;Kalach et al, 2007;Koletzko et al, 2006;Toracchio & Marzio, 2003;Tüzün et al, 2008). With the increasing number of prescriptions for H. pylori eradication and the involvement of new treatment regimens, post-treatment resistance to amoxicillin, tetracycline and quinolones has also been reported (Hsu et al, 2008;Koletzko et al, 2006;Nishizawa et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of H. pylori strains with secondary resistance to clarithromycin was much higher than strains with primary resistance in the same population. However, few studies focused on this tough problem in children, and the rates of secondary clarithromycin resistance varied from 14.2% up to 78% .…”
Section: Prevalence Of Clarithromycin‐resistant Helicobacter Pylori Imentioning
confidence: 99%